2004
DOI: 10.1002/anie.200460045
|View full text |Cite
|
Sign up to set email alerts
|

Readily Available Onio‐Substituted Methyleneiminium Salts: Single Precursors for a Variety of Aminocarbenes

Abstract: Due to their strong s-donor properties, N-heterocycliccarbenes (NHCs) have found numerous applications as ligands for transition-metal catalysts.[1] More recently, it has been found that acyclic diaminocarbenes A (see Scheme 1) [2] or even amino aryl carbenes B[3] also behave as strong-sdonor weak-p-acceptor ligands and therefore could be considered as alternative ligands for catalysts; [4,5] to date, A is the most basic carbene ligand known.[4c] However, the range of acyclic amino carbenes (AAC) known is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…We have already shown that highly thermally stable phosphonio-substituted aldiminium salts 1 [11] are readily prepared in excellent yields by addition of phosphines to Alder's dimer, [12] or alternatively by treatment of the corresponding chloro aldiminium salt with the in situ generated phosphine/trimethylsilyl triflate adduct. [13] Interestingly, basic phosphines, such as tricyclohexylphosphine, are not required, triphenylphosphine can be used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have already shown that highly thermally stable phosphonio-substituted aldiminium salts 1 [11] are readily prepared in excellent yields by addition of phosphines to Alder's dimer, [12] or alternatively by treatment of the corresponding chloro aldiminium salt with the in situ generated phosphine/trimethylsilyl triflate adduct. [13] Interestingly, basic phosphines, such as tricyclohexylphosphine, are not required, triphenylphosphine can be used.…”
Section: Resultsmentioning
confidence: 99%
“…After evaporation of the solvent, the residue was extracted with pentane, and ylide 2a was isolated in near quantitative yield. We then used dication 1b, [11] featuring the less basic triphenylphosphine. Under the same experimental conditions, but with tetrakis (dimethylamino)ethylene (TDAE) as a reducing agent, we observed the quantitative formation of triphenylphosphine and alkene 3b, the expected dimer of the (diisopropylamino) (hydrogeno)carbene (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest in this study, another amido reagent, the thermally highly stable lithium diphenylamide (LiNPh 2 ), has shown promise in a range of synthetic transformations. As well as regioselective deprotonation reactions, [6][7][8][9][10] it has also been used in catalytic aldol reactions involving silyl enol ethers and aldehydes; [11,12] in elimination applications; [13,14] in metathetical reactions; [15][16][17][18][19][20][21][22][23][24][25][26][27] during the preparation of amino-containing carbenes, [28] and as an initiator in the polymerisation of methyl methacrylate. [29] utilised as the metallating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, they are valuable subjects for solution of a number of structural problems 1,2 and development of the organophosphorus synthesis. [3][4][5] In particular, they are of use in the synthesis of stable aminophosphine carbene ligands for metal com plexes with potential catalytic activity. 5 In the present communication, a new reaction that is promising for the synthesis of complex phosphine compounds is presented.…”
mentioning
confidence: 99%